2008
DOI: 10.1007/s11999-008-0356-7
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Chordoma: Can Local Recurrence After Sacrectomy Be Predicted?

Abstract: Surgical resection margins are reportedly the most important predictor of survival and local recurrence with sacral chordomas. We examined the relevance of invasion of the surrounding posterior pelvic musculature (piriformis and gluteus maximus) at initial diagnosis to local recurrence after sacrectomy. We retrospectively reviewed 18 patients with histologically verified sacral chordoma seen at our institution between 1998 and 2005. There were 14 men and four women with a mean age of 65.1 years (range, 31-78 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 34 publications
4
74
1
2
Order By: Relevance
“…Hanna et al 16 suggested infiltration of the musculature adjacent to the sacrum and/or involvement of the sacroiliac joints increases the tendency of local recurrence, even after apparently successful en bloc resection of the tumor. All patients with invasion of the surrounding muscle had The role of traditional radiation remains controversial because chordomas are not very radiosensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Hanna et al 16 suggested infiltration of the musculature adjacent to the sacrum and/or involvement of the sacroiliac joints increases the tendency of local recurrence, even after apparently successful en bloc resection of the tumor. All patients with invasion of the surrounding muscle had The role of traditional radiation remains controversial because chordomas are not very radiosensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Bergh et al [3] reported a 37% local recurrence rate at a median of 8 years of followup. Baratti et al [2], Hulen et al [24], and Hanna et al [20] reported local recurrence rates of 54%, 56%, and 60%, respectively, at mean followups of 5.9, 5.5, and 4.4 years, respectively, after wide resection. Fuchs et al [13] reported an excellent recurrence rate of 5% in 21 patients who all received wide resection.…”
Section: Figmentioning
confidence: 98%
“…Its minimal response to chemo-and radiotherapy [6,13] makes surgery the treatment of choice [14,47]. Local recurrence rates range from 43% to 85% [2,4,5,20,26,29,31,56,57] depending on the surgical margins obtained at initial Each author certifies that he or she has no commercial associations (eg, consultancies, stock ownership, equity interest, patent/licensing arrangements, etc) that might pose a conflict of interest in connection with the submitted article. Each author certifies that his or her institution has approved the reporting of these cases, that all investigations were conducted in conformity with ethical principles of research, and that informed consent for participation in the study was obtained.…”
Section: Introductionmentioning
confidence: 99%